The variability of the economically-valuable characteristics of soybean in the conditions of the Left Bank Forest-Steppe of Ukraine - Biliavska , L.H.; Rybalchenko , A.M. (Scientific Progress & Innovations, 2019)
The aim of the article is to establish the variability level of economically-valuable characteristics of soybean genotypes under the conditions of the Left-Bank Forest-Steppe of Ukraine. It is necessary to improve the selection methods for the efficient work, aimed at creating highly-productive varieties. Moreover, it is important to establish the variability level of soybean varieties and variety samples. Methods of the research. The following methods were used to substantiate scientifically the purpose, implement the established tasks and summarize the research results: general-scientific (studying the direction of the research, planning and carrying out the experiment; conducting observations); special (field – to observe phenological development stages and the condition of plants; laboratory (measuring-weighing) – to determine structural indices and plant productivity, to detect economically-valuable plant signs); mathematical-statistical (to process experimental data, determine the parameters of variability signs and define the significance of the obtained results). The research results. The research results of studying the variability of economically-valuable characteristics of soybean under the conditions of the Left-Bank Forest-Steppe of Ukraine have been given in the article. It has been established that the following characteristics have a high level of variability: the seed weight per plant (V=22.8%) and the number of pods on a plant (V=22.9%). Such characteristics as the number of seeds per plant (V=16.4%), the weight of 1000 seeds (V=11.1%), plant height (V=13.4%), and also the height of the lower pod attachment (V=17.1%) are characterized by the average level of variability. The elements of scientific novelty. It has been proved that based on the detailed studying the quantitative signs’ variability of soybean genotypes, it is possible to conduct effectively the selection work in creating highly productive varieties. In the selection process one should be oriented at stable indices of quantitative signs. In our research these are: the number of seeds per plant, the weight of 1000 seeds, plant height, and the height of the lower pod attachment. Practical importance. Studying the variability of economically-valuable characteristics of soybean ensures the effective selection.